Determination of Residual Nonsteroidal Anti-Inflammatory Drugs in Aqueous Sample Using Magnetic Nanoparticles Modified with Cetyltrimethylammonium Bromide by High Performance Liquid Chromatography - Malihe Khoeini Sharifabadi; Mohammad Saber-Tehrani; Syed Waqif Husain; Ali Mehdinia; Parviz Aberoomand-Azar (The Scientific World Journal)
A simple and sensitive solid-phase extraction method for separation and preconcentration of trace amount of four nonsteroidal anti-inflammatory drugs (naproxen, indomethacin, diclofenac, and ibuprofen) using Fe3O4 magnetic nanoparticles modified with cetyltrimethylammonium bromide has been developed. For this purpose, the surface of MNPs was modified with cetyltrimethylammonium bromide (CTAB) as a cationic surfactant. Effects of different parameters influencing the extraction efficiency of drugs including the pH, amount of salt, shaking time, eluent type, the volume of solvent, amount of adsorbent, sample volume, and the time of desorption were investigated and optimized. Methanol has been used as desorption solvent and the extracts were analysed on a reversed-phase octadecyl silica column using 0.02 M phosphate-buffer (pH = 6.02) acetonitrile (65 : 35 v/v) as the mobile phase and the effluents were measured at 202 nm with ultraviolet detector. The relative standard deviation (RSD%) of the method was investigated at three concentrations (25, 50, and 200 ng/mL) and was in the range of 3.98–9.83% (n=6) for 50 ng/mL. The calibration curves obtained for studied drugs show reasonable linearity (R2>0.99) and the limit of detection (LODs) ranged between 2 and 7 ng/mL. Finally, the proposed method has been effectively employed in extraction and determination of the drugs in biological and environmental samples.